Perceived Risk on Consumer Online Shopping Behaviour - Endah Setya Octaviani; Hendra Gunawan (Journal of Applied Accounting and Taxation, 2018)
This study aims to determine the effect of perveived risk on consumer online shopping behavior of fashion product. The significant difference presented are the product category, using the category of fashion product as the most demand category by consumers. Samples used are students in the field of accounting at universities. The result of this research are there is negative influence of perception of product risk to customer satisfaction and re-purchased intention. The perveived cost risk has no negative effect on satisfaction and re-purchased intention. Perception of individual risk do not have a negative effect on customer satisfaction and re-purchased intention.